Large-scale social and behavior change communication interventions have sustained impacts on infant and young child feeding knowledge and practices: Results of a 2-year follow-up study in Bangladesh - Kim, Sunny S.; Nguyen, Phuong Hong; Tran, Lan Mai; Sanghvi, Tina; Mahmud, Zeba; Haque, Mohammad Raisul; Afsana, Kaosar; Frongillo, Edward A.; Ruel, Marie T.; Menon, Purnima (Elsevier, 2018)
Sustained improvements in infant and young child feeding (IYCF) require continued implementation of effective interventions. From 2010–2014, Alive & Thrive (A&T) provided intensive interpersonal counseling (IPC), community mobilization (CM), and mass media (MM) in Bangladesh, demonstrating impact on IYCF practices. Since 2014, implementation has been continued and scaled up by national partners with support from other donors and with modifications such as added focus on maternal nutrition and reduced program intensity.